2021
DOI: 10.18632/aging.202547
|View full text |Cite
|
Sign up to set email alerts
|

MET inhibitor, capmatinib overcomes osimertinib resistance via suppression of MET/Akt/snail signaling in non-small cell lung cancer and decreased generation of cancer-associated fibroblasts

Abstract: Background: Patients with non-small cell lung cancer (NSCLC) initially responding to tyrosine kinase inhibitors (TKIs) eventually develop resistance due to accumulating mutations in the EGFR and additional lesser investigated mechanisms such as the participation of the tumor microenvironment (TME). Methods: Here, we examined the potential for MET inhibitor capmatinib for the treatment of osimertinib-resistant NSCLCs and normalizing the TME. Results: We first established that HCC827 and H1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Osimertinib is a relatively specific inhibitor of mutant active forms of ERBB1 and is, at present, the standard of care therapeutic. As with all targeted drugs in cancer, eventually NSCLC cells become osimertinib resistant, with diverse mechanisms, including gain of additional ERBB1 mutations or activation of other receptor tyrosine kinases such as c-MET and FGFRs (15)(16)(17)(18). Overcoming osimertinib resistance remains an important area for the developmental cancer therapeutics field in NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Osimertinib is a relatively specific inhibitor of mutant active forms of ERBB1 and is, at present, the standard of care therapeutic. As with all targeted drugs in cancer, eventually NSCLC cells become osimertinib resistant, with diverse mechanisms, including gain of additional ERBB1 mutations or activation of other receptor tyrosine kinases such as c-MET and FGFRs (15)(16)(17)(18). Overcoming osimertinib resistance remains an important area for the developmental cancer therapeutics field in NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Blockade of c-MET promoted a reduction in cell growth and proliferation in their analysis. Similarly, Zhu et al reported on the augmented expression of c-MET in non-small cell lung cancer cell lines with osimertinib resistance as compared to sensitive ones [ 36 ]. Treating resistant cells with the c-MET inhibitor capmatinib reduced EMT and self-renewal ability as well as promoting cell re-sensitization to osimertinib.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibiting the classical NF-κB signaling pathway blocks growth hormone (GH) or insulin-like growth factor (IGF-1) signaling, suppresses cell proliferation, and suppresses bone morphogenetic protein 2 (BMP2) expression, thereby promoting apoptosis (Jimi et al, 2019). Most importantly, these three genes were all involved a lot in the inflammatory response (Zhang Z. et al, 2021;Zhu et al, 2021;Li et al, 2022), stating that inflammatory response was a main regulated pathway in IPF and these three genes could modulate the pathological process of IPF through this pathway.…”
Section: Discussionmentioning
confidence: 99%